Diversification of processed miana leaves for community empowerment in Sokkolia Village, Gowa Regency - A. Irma Suryani; Andi Asmawati Azis; A. Bida Purnamasari; Hilda Karim; Irma Suryani Idris; Ahmad Fudhail Majid (Journal of Community Service and Empowerment, 2022)
A healthy lifestyle is an effort made to keep the body healthy and fit. One of the healthy lifestyles is consuming vegetables and fruit. In accordance with one of the goals of sustainable development (SDGs), namely a healthy and prosperous life and economic growth, the focus of this activity is on the health and welfare of the community by utilizing the processing of minasa leaves through diversification of miana leaves into various food preparations. This training was held in Sokkolia Village, Gowa Regency. Residents were given hands-on material and practice regarding miana leaf processing. After the training, a questionnaire was given to determine the participant's response to this training. The results of the questionnaire obtained an average score of 4.22. This means that the implementation of activities is in good criteria.